2015
DOI: 10.1021/acsami.5b08607
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Cryogel Matrix and Temperature-Reversible Soluble–Insoluble Polymer for the Development of in Vitro Human Liver Tissue

Abstract: Hepatic cell culture on a three-dimensional (3D) matrix or as a hepatosphere appears to be a promising in vitro biomimetic system for liver tissue engineering applications. In this study, we have combined the concept of a 3D scaffold and a spheroid culture to develop an in vitro model to engineer liver tissue for drug screening. We have evaluated the potential of poly(ethylene glycol)-alginate-gelatin (PAG) cryogel matrix for in vitro culture of human liver cell lines. The synthesized cryogel matrix has a flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…Studies have shown that the pore size of bioscaffolds is crucial for determining their function, with smaller pores providing better nutrient and oxygen transfer to facilitate cell growth and proliferation, while large pores provide a high surface area to accommodate cells. 48 Bioscaffolds with a larger mean pore sizes (i.e., 300 mm) have also been shown to be associated with a significantly higher cell viability and proliferation relative to bioscaffolds with a smaller mean pore size. 49 In keeping with these studies, structural analysis of our collagen bioscaffold demonstrated it to have a mean pore size of 300 6 100 mm, which we have shown facilitates AD-MSCs viability and proliferation, especially when compared to AD-MSCs cultured on conventional 2D culture plates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the pore size of bioscaffolds is crucial for determining their function, with smaller pores providing better nutrient and oxygen transfer to facilitate cell growth and proliferation, while large pores provide a high surface area to accommodate cells. 48 Bioscaffolds with a larger mean pore sizes (i.e., 300 mm) have also been shown to be associated with a significantly higher cell viability and proliferation relative to bioscaffolds with a smaller mean pore size. 49 In keeping with these studies, structural analysis of our collagen bioscaffold demonstrated it to have a mean pore size of 300 6 100 mm, which we have shown facilitates AD-MSCs viability and proliferation, especially when compared to AD-MSCs cultured on conventional 2D culture plates.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Our bioscaffold also has a high degree of porosity (75% ± 3%) with a corresponding high swelling ratio. 48 The high porosity and interconnected macropores of our bioscaf-fold creates a physical space to facilitate cell movement and distribution throughout the bioscaffold. In turn, this is advantageous for nutrient and oxygen transfer to all cells seeded into the bioscaffold while also preventing cell loss from cellular overcrowding, which commonly occurs when using traditional cell culture plates.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, PDMS provides a suitable “base-biomaterial” for the fabrication of porous 3D bioscaffolds. Studies have shown that the pore size of 3D bioscaffolds is crucial for determining their function—small pores provide better nutrient and oxygen transfer to facilitate cell growth and proliferation and large pores (i.e., ≥ 300 μm) provide a high surface area to accommodate cells while also facilitating their viability and rate of proliferation [38, 39]. Structural analysis of our PDMS bioscaffold demonstrated it to have a mean pore size of 300 ± 100 μm with a corresponding increase in AD-MSC viability and proliferation compared to AD-MSCs cultured on conventional 2D culture plates.…”
Section: Discussionmentioning
confidence: 99%
“…Kumari et al used cryogel matrix combined with temperature‐reversible soluble–insoluble polymer as the scaffold for in vitro culture of liver cells. The developed spheroid structure displayed liver‐specific functions as well as morphological features such as intercellular bile canalicular lumen (Kumari, Karande, & Kumar, ). Takebe et al produced 3D liver buds by self‐organization of human iPSCs‐derived hepatocytes and transplanted the liver buds into mice, which displayed functional vasculature connecting to the host.…”
Section: Application Of Construction Strategies In Solid Organ Tissuementioning
confidence: 99%